PENGARUH KEPRIBADIAN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI BANK SULUT GO CABANG GORONTALO - Idrus Usu (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
This study aims to determine the influence of personality and emotional intelligence on the performance of employees of Bank SulutGo Branch Gorntalo. The data used in this research is primary data that comes from the questionnaire filling. The population of the study was 47 employees using census method. The analytical technique used to answer the research problem and test bthe hypothesis is multiple regression analysis with the help of Statistical Package Social Science (SPSS) software used to analyze the data. Before performing the hypothesis test, validity and reliability test of the instrument followed by testing the requirements of regression analysis. The findings of this research are (1) there are positive and significant influences Personality to Employees Performance of Bank SulutGo Branch Gorontalo, (2) there is positive and sifnificant influence Emotional Intelligence to Employees Performance of Bank SulutGo Branch Gorontalo. Tests simultaneously show that the personality and Emotional intelligence have a positive ang sifnificant impact on the performance of employees of Bank SulutGo Branch Gorontalo. The dominant variabel affecting employees performsnce of Bank SulutGo Branch Gorntalo is emotional intelligence